2010
DOI: 10.1002/bmc.1382
|View full text |Cite
|
Sign up to set email alerts
|

Development of an HPTLC‐based diagnostic method for invasive aspergillosis

Abstract: A rapid, sensitive and specific high-performance thin-layer chromatographic (HPTLC) method was developed and validated for determination of gliotoxin in Aspergillus infected immunocompromised patients with invasive aspergillosis (IA). Densitometric analysis of gliotoxin was carried out in the absorbance mode at 254 nm after single-step extraction with chloroform. The method uses TLC aluminum plates pre-coated with silica gel 60F-254 as a stationary phase and toluene-isoamyl alcohol-methanol (10:0.5:0.5, v/v/v)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Additionally, these mutants show reduced virulence in non-neutropenic murine models but not neutropenic models [6], [18][20]. This toxin and/or its derivatives are also considered for use for diagnosis of IA [21], [22]. Aside from gliZ, no other transcription factors have been described to regulate the gli cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these mutants show reduced virulence in non-neutropenic murine models but not neutropenic models [6], [18][20]. This toxin and/or its derivatives are also considered for use for diagnosis of IA [21], [22]. Aside from gliZ, no other transcription factors have been described to regulate the gli cluster.…”
Section: Introductionmentioning
confidence: 99%
“…The sample pretreatment for LC-MS is quick and easy. Other methods for determining BAs were excluded because of false positives [22]. The standard addition recovery test showed that HPLC-MS/ MS has higher sensitivity and a detection limit down to lower level compared with the current conventional liquid phase standard procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These include the surface protein Cf2, which was isolated from a human patient with proven IA and is also present in growing hypha of A. fumigatus but not in spores [107] as is Asp f6/MnSOD [108], gliotoxin, which is produced by most A. fumigatus strains and is present in plasma and serum [109] and its inactive derivative bis(methylthio)gliotoxin, which is also recoverable from blood [110], 15 immunogenic proteins of the immunosecretome [111] and secreted proteases whose activity in serum specimens might serve as a new diagnostic approach if used with reporter peptides [112].…”
Section: Other Biomarkersmentioning
confidence: 99%